MRI Atlas Orthopedics and Neurosurgery, The Spine - Weyreuther, Martin; Heyde, Christoph E.; Westphal, Michael; Zierski, Jan; Weber, Ulrich (Springer Berlin Heidelberg : Imprint: Springer, 2007)
This MRI atlas of the spine is the fruit of interdisciplinary cooperation among radiologists, orthopedic surgeons, traumatologists, and neurosurgeons. It is a clinically oriented atlas that covers all important diseases and injuries of the spine. Ample illustrations are supplemented by concise descriptions of anatomy and pathophysiology, the normal and abnormal MRI appearance, diagnostic pitfalls, and the clinical significance of MRI. The clear and didactic style enables readers to revise the fundamentals of spinal anatomy and disease states as a basis for understanding the diagnostic strategies and surgical management. By combining descriptions of the clinical manifestation of spinal disorders with the corresponding MRI findings, the authors hope to help readers develop a meaningful approach to the interpretation of MRI of the spine.